Pharmacokinetic study of bortezomib administered intravenously in Taiwanese patients with multiple myeloma. Issue 1 (19th June 2017) - Huang, Shang‐Yi; Chang, Cheng‐Shyong; Liu, Ta‐Chih; Wang, Po‐Nan; Yeh, Su‐Peng; Ho, Ching‐Liang; Kuo, Ming‐Chung; Lin, Hsuan‐Yu; de Jong, Jan; Chen, Jia‐Yi; Yang, Ya‐Wen
Abstract: This phase 4, single‐arm, non‐randomized, open‐label, post approval commitment study evaluated the pharmacokinetics and safety of bortezomib in Taiwanese patients with multiple myeloma. Patients (≥20 years) with measurable secretory multiple myeloma (serum monoclonal IgG ≥10, IgA/IgE ≥5, IgD ≥0.5 g/L, IgM present [regardless of level], and urine M protein of ≥200 mg/24 h) received intravenous bortezomib 1.3 mg/m 2, twice weekly for 2 weeks, followed by a 10‐day resting phase (days 12 to 21). Pharmacokinetics and safety were assessed at pre‐specified time points. All enrolled patients (n = 18, men: 11; women: 7) completed the study. Mean (SD) Cmax (maximum observed plasma concentration) on day 11 was 266 (77.5) ng/mL, approximately 60% higher compared with non‐Asian patients receiving a similar bortezomib regimen but with overlapping ranges. Because of the protracted terminal phase, half‐life (t1/2 ), area under the plasma concentration‐time curve from time 0 to infinity (AUC∞ ), volume of distribution (Vz ), and systemic clearance were not assessable. All patients experienced treatment‐emergent adverse events (TEAEs); 78% were drug‐related. Most commonly reported TEAEs were thrombocytopenia (n = 11 [61%]), neutropenia (n = 9 [50%]), leukopenia (n = 6 [33%]), and diarrhoea (n = 6 [33%]); the most common serious adverse event was pneumonia (n = 2 [11%]). One patient had a dose reduction due to a TEAE of thrombocytopenia. Overall, bortezomib exposure (AUC) in Taiwanese patients (AUClast [SD]: 230 [147] ng·h/mL) with twice weekly intravenous administration was comparable with non‐Asian population (AUClast [SD]: 241 [82] ng·h/mL). Bortezomib treatment was associated with manageable toxicity profile and did not limit the continuity of therapy.